KAJIAN REMINISCENCE GROUP THERAPHY PADA DEPRESI LANSIA WANITA YANG TINGGAL DI PANTI WERDHA - Feny Mega Lestari; Elmira N. Sumintardja (MANASA, 2016)
Depression is a mood disorder commonly experienced by the elderly. Elderly who evaluate their past experiences as failure, guilt, anger, discontent and desperation will usually fall into depression. Number of depression found in elderly women tends to be higher in comparison to that of the elderly men. Elderly living in nursing houses tend to experience depression more than ones who live with the family. The aim of this study was to observe the effect of reminiscence group therapy in reducing depression experienced by the elderly women who live in nursing houses. Study conducted on a group of eight elderly women living in SA Nursing House, Jakarta. Method used is a Quasi Experimental Research with one-group pre-post design. Measuring tools used are Modified Mini Mental State Test (3ms) for the selection of participants with mild or moderate dementia category, and Geriatric Depression Scale - Short Form (GDS-SF) to determine the level of depression of the participants before and after reminiscence group therapy. The results showed that the reminiscence group therapy was successfully implemented and effective in reducing the rate of depression in the group of elderly women living in SA Nursing House, Jakarta. This is evident from a decrease in depression scores and a decrease in the number of symptoms of depression in participants that were measured by using a GDS-SF after the implementation of reminiscence group therapy.